A flow-of-funds perspective on the financial crisis : volume II: macroeconomic imbalances and risks to financial stability - Winkler, Bernhard; Riet, Ad van.; Bull, Peter; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Based on the crisis experience, the book offers an overview of lessons for macrofinancial analysis and financial stability. It illustrates the interlinkages between the financial side and the real side of the economy and highlights the role of balance sheet variables and sectoral balance sheet positions in the evolution of the financial crisis.
Keywords: Business; Business enterprises -- Finance; Finance; Banks and banking; Accounting; Macroeconomics; Economic policy; Business and Management